2015
DOI: 10.1111/ajco.12344
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial concerns of cancer patients in Singapore

Abstract: Distress and psychosocial needs are high in cancer patients even at an early stage prior to chemotherapy. Attention to these needs is crucial as they cause significant distress and affect the patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…Our study results suggest that a case management programme should involve assessment of a patient's physical condition and underlying disease is essential before treatment. The current study also indicated that refusing treatment was influenced by a patient, their families, or friend's experience of negative treatment effects and worry about the side effects of treatment, which is consistent with the results of previous study that identified psychosocial factors as a significant element in compliance with treatment (Ayres et al, 1994;Mahendran et al, 2015;Maric et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study results suggest that a case management programme should involve assessment of a patient's physical condition and underlying disease is essential before treatment. The current study also indicated that refusing treatment was influenced by a patient, their families, or friend's experience of negative treatment effects and worry about the side effects of treatment, which is consistent with the results of previous study that identified psychosocial factors as a significant element in compliance with treatment (Ayres et al, 1994;Mahendran et al, 2015;Maric et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…These psychosocial factors included anxiety (Greer, Pirl, Park, Lynch, & Temel, 2008;Maric et al, 2010), depression, poor emotional and mental functioning (Maric et al, 2010), guilt and hostility (Ayres et al, 1994). A previous study revealed that distress and psychosocial needs (worry, fear, nervousness and sadness) are high in cancer patients at early stage, prior to chemotherapy (Mahendran, Lim, Chua, Lim, & Kua, 2015).…”
Section: Discontinuing Treatment and Related Factorsmentioning
confidence: 99%
“…First, a large number of patients were uninterested in participating in this study because they found such research onerous. This is characteristic of research conducted with the local cohort of cancer patients receiving active treatment and within 3 months of their diagnosis; regardless, a more cautious interpretation of the findings are warranted. Cross‐cultural comparisons should note that locally validated cut‐offs were used.…”
Section: Discussionmentioning
confidence: 99%
“…Such symptoms may often go undetected and untreated even over time, leading to persistent distress . This is worrying given that, in Singapore at least, levels of subsyndromal anxiety and depression in cancer outpatients were between 15% and 16% at first visit to the oncologist, and 80% reported at least one unmet emotional concern . It is imperative to document longitudinally the prevalence rates of subsyndromal anxiety and depression in Asian patients before these symptoms develop into comorbid psychiatric disorders that pose a greater risk for downstream management, and attempt to identify patients at risk for anxiety and depression early in the cancer journey …”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, a country that is culturally similar to Singapore, it was found that having formal support in caregiving (such as having a domestic maid or a private nurse) did not alleviate the burden of family caregivers who were caring for dementia patients, emphasising the value of providing familial care. (23) It is also possible that Asian patients experience more severe symptoms of emotional stress and unmet needs (24) as compared to their Western counterparts or the general population. (25) This may influence the caregiver's emotional well-being and result in QOL impairments, as it exacerbates the negative perception of providing care and increases role strain.…”
Section: Discussionmentioning
confidence: 99%